2014
DOI: 10.1002/ajp.22261
|View full text |Cite
|
Sign up to set email alerts
|

Highly nested diets in intrapopulation monkey–resource food webs

Abstract: Recently several studies have focused on the structure of ecological networks to provide insights into ecological and coevolutionary dynamics of interacting species. However, rarely have the tools of ecological networks been used to understand how feeding relationships vary among individuals of the same population. Here we use 7 years of data and network analyzed to examine the intrapopulation diet variation in a group of howler monkeys (Alouatta palliata). We show that individual monkey-resource food webs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 64 publications
0
10
0
Order By: Relevance
“…Variation in pollinator visitation frequency to flowers can generate complex networks among individuals of the same plant species. Similar studies have been conducted involving individual-based networks in other interaction systems using an intrapopulation approach, such as sea otters-prey, didelphid marsupials-arthropods, snails and fruits, monkeys-fruiting plants, frogs, ant-plants, and lizards-diets [ 28 , 29 , 30 , 31 , 32 , 33 ]. However, to our knowledge only two studies have evaluated the networks of plant-pollinator interactions among individuals within populations [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 96%
“…Variation in pollinator visitation frequency to flowers can generate complex networks among individuals of the same plant species. Similar studies have been conducted involving individual-based networks in other interaction systems using an intrapopulation approach, such as sea otters-prey, didelphid marsupials-arthropods, snails and fruits, monkeys-fruiting plants, frogs, ant-plants, and lizards-diets [ 28 , 29 , 30 , 31 , 32 , 33 ]. However, to our knowledge only two studies have evaluated the networks of plant-pollinator interactions among individuals within populations [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 96%
“…Adults, though, consumed the greatest variety of plant species and items. Male and female infants tended to consume more plant species in continuous forest than in fragments, whereas adult females were the most extreme "generalists" in the resulting networks (Dáttilo et al 2014). This study is the first one to show that the specialized diets of male and female infants determined the nested structure of primate-plant networks in howler monkey populations.…”
Section: Habitat Food Choice and Availabilitymentioning
confidence: 65%
“…In our intrapopulation networks, plant species and monkeys are depicted as nodes, and their feeding interactions are depicted by links describing the use of plant species by individuals. Our qualitative approach in calculating nestedness decreases the probability of overestimating the amount of resources (e.g., leaves vs. fruits) ingested by monkeys (Dáttilo et al, 2014).…”
Section: Network Metricsmentioning
confidence: 99%
“…In our intrapopulation networks, plant species and monkeys are depicted as nodes, and their feeding interactions are depicted by links describing the use of plant species by individuals. Our qualitative approach in calculating nestedness decreases the probability of overestimating the amount of resources (e.g., leaves vs. fruits) ingested by monkeys ( Dáttilo et al, 2014 ). Biologically, nestedness describes the organization of niche breadth in which more nested networks tend to have the highest niche overlap ( Blüthgen, 2010 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have used tools derived from network analysis to describe the dietary variation found in populations of animals with a focus on individual-based plant-animal networks ( Pires et al, 2011 ; Tinker et al, 2012 ; Cantor et al, 2013 ). Recently, it has been shown that intrapopulation primate-resource networks are highly nested: diets of specialist individuals are a subset nested within the diets of generalist individuals ( Dáttilo et al, 2014 ). There is no information, however, about potential factors determining such network structure.…”
Section: Introductionmentioning
confidence: 99%